Pemberdayaan Ekonomi Masyarakat Nelayan di Kampung Mumes Raja Ampat Papua Barat - Muchlashin, Anif; Putri, Widya Astika; Asya’bani, Nispia; Nurfajrin, Siti (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
This study focuses on discussing empowerment activities carried out in eastern Indonesia, West Papua to be exact. Researchers found a problem that occurred, namely the lack of strength of human resources which then became the focus in carrying out empowerment activities in this study. This is inversely proportional to the state of natural resources which are very rich and abundant which should be one of the forces to improve the welfare of the people of Kampung Mumes. The researcher uses the PAR (Participatory Action Research) methodology as a research method. The systematics of PAR are to know, to understand, to plan and to action. The PAR methodology is oriented towards community empowerment, namely efforts to create community independence. Through the research approach used, it is known that the root of the problem is the lack of community competence in processing natural resources in the form of fish obtained from the sea around them. Through this empowerment activity, capacity building has been carried out by conducting fish processing training, making noken and making meatballs and nuggets to improve the welfare of the community in Mumes Village. Keywords: community empowerment, economic improvement, fisherman. Abstrak: Penelitian ini berfokus membahas tentang kegiatan pemberdayaan yang dilakukan di Indonesia bagian timur, tepatnya Papua Barat. Peneliti menemukan masalah yang terjadi yakni kurangnya kekuatan sumber daya manusia yang kemudian menjadi fokus dalam melakukan kegiatan pemberdayaan pada penelitian ini. Hal ini berbanding terbalik dengan keadaan sumber daya alam yang sangat kaya dan melimpah ruah yang seharusnya dapat menjadi salah satu kekuatan untuk meningkatkan kesejahteraan masyarakat Kampung Mumes. Peneliti menggunakan metodologi PAR (Participatory Action Research) sebagai metode penelitian. Sistematika dari PAR adalah to know, to understand, to plan dan to action. Metodologi PAR berorientasi untuk pemberdayaan masyarakat yakni upaya untuk menciptakan kemandirian masyarakat. Melalui pendekatan penelitian yang digunakan diketahui akar permasalahannya adalah kurangnya kompetensi masyarakat dalam mengolah sumber daya alam berupa ikan yang didapatkan dari laut yang berada di sekitaran mereka. Melalui kegiatan pemberdayaan ini telah dilakukan peningkatan kemampuan dengan melakukan pelatihan pengolahan ikan, melakukan pembuatan noken dan pembuatan bakso serta nugget untuk meningkatkan kesejahteraan masyarakat di Kampung Mumes.